Low antitubercular drug levels in newly infected normal hosts - Jiaranai Khantipongse (2018)
Background: Low antitubercular drug level is a risk factor for treatment failures. Antitubercular drug level determination has been suggested for complicated tuberculosis patients, but there has been interest in performing such studies in normal hosts. Objective: To identify whether there are advantages of routine antitubercular drug level determination. Patients and Methods: We determined drug levels in 15 new normal host Thai tuberculosis patients by using published methods. All patients received the Directly Observed Treatment Short-course including pyrazinamide, rifampicin, and isoniazid. Results: We started with 15 patients of whom 27% (4 patients) were mycobacteria smear-positive, 33% (5 patients) had low blood levels of pyrazinamide and 87% had low levels of rifampicin. The drug levels in the smear-positive group were lower than in the smear-negative group. All smear-positive patients had a rifampicin levels lower than the therapeutic range. Conclusion: Antitubercular drug level determination has a potential to identify patients who may be at risk of poor treatment results.